Financial innovation practice, sacco size and financial sustainability of deposit taking saving and credit co-operatives in Kenya - Justus Nderitu Maina; Richard Muthii Kiai; Teresia Ngina Kyalo (Financial Studies, 2020)
The study aimed at assessing the moderating effect of SACCO size on the nexus between financial innovation practice and financial sustainability which was anchored on transaction cost innovation theory. The population for the study was the Deposit Taking Saving and Credit Co-operatives in Kenya. The study adopted a philosophical paradigm of positivism and descriptive cross-sectional survey design where the sample size was 119 respondents out of which 113 responded. Emailed questionnaire and data collection sheet were used in data collection. The study found that the process innovation and service innovation are positively related to financial sustainability but not statistically significant. This study concluded that SACCO size is statistically significant in moderating financial innovation practice and financial sustainability of Deposit Taking Saving and Credit Co-operatives in Kenya. The study recommends that Deposit Taking Saving and Credit Co-operatives should continue to invest in new and promising process and service innovation strategies to continue realizing the benefits of financially sustainable enterprise.
Keywords: G21; O32; P13; 330; Process innovation; Service innovation; Financial Self-sufficiency; Total assets